2015
DOI: 10.1016/j.dci.2014.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Reprint of “Evolution of specific immunity in shrimp – A vaccination perspective against white spot syndrome virus”

Abstract: Invertebrates lack true adaptive immunity and it solely depends on the primitive immunity called innate immunity. However, various innate immune molecules and mechanisms are identified in shrimp that plays potential role against invading bacterial, fungal and viral pathogens. Perceiving the shrimp innate immune mechanisms will contribute in developing effective vaccine strategies against major shrimp pathogens. Hence this review intends to explore the innate immune molecules of shrimp with suitable experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 109 publications
0
6
0
Order By: Relevance
“…As a consequence, it is not possible to develop vaccines in the traditional way as is done in mammals and other vertebrates. However, recent developments have provided evidence that certain forms of pathogen-specific “immune priming” are possible in some invertebrates [ 210 ]. For example, short-term protection against WSSV can be achieved through exposing shrimp to inactivated viral particles [ 211 ].…”
Section: Current Treatment Options For Wsdmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, it is not possible to develop vaccines in the traditional way as is done in mammals and other vertebrates. However, recent developments have provided evidence that certain forms of pathogen-specific “immune priming” are possible in some invertebrates [ 210 ]. For example, short-term protection against WSSV can be achieved through exposing shrimp to inactivated viral particles [ 211 ].…”
Section: Current Treatment Options For Wsdmentioning
confidence: 99%
“…For example, short-term protection against WSSV can be achieved through exposing shrimp to inactivated viral particles [ 211 ]. Musthaq and Kwang reviewed the possibilities of such vaccinations for WSD and the types of treatments (vaccines) that can provide temporal protection against WSD [ 210 ]. These include inactivated virus, recombinant viral proteins, viral DNA, and double-stranded RNA, and often involve WSSV envelope proteins like VP28 because of their importance to the infection process.…”
Section: Current Treatment Options For Wsdmentioning
confidence: 99%
“…Invertebrates include a wide variety of species, accounting for more than 95% of the animal kingdom ( 14 ). Invertebrate immunology has attracted more and more attention, and with the further study of invertebrate immune priming, some mechanisms have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…No medicines yet to prove effective against WSSV; hence, finding ways to combat this shrimp pathogen now become to be indispensable. Oral vaccination with two structural proteins: VP19 and VP466, were unsuccessful in term of reducing mortality and envelope protein VP28 experimentally elicited the immune response by only some degrees (Ha et al, 2008;Syed Musthaq & Kwang, 2015). Another study with recombinant VP292 protein vaccine also showed unsatisfactory results in-vivo (mortality >50%) (Zhu, Du, Miao, Quan, & Xu, 2009).…”
Section: Introductionmentioning
confidence: 99%